Risk factors for posttraumatic stress disorder: An umbrella review of systematic reviews and meta-analyses. (December 2019) - Tortella-Feliu, Miquel; Fullana, Miquel A.; Pérez-Vigil, Ana; Torres, Xavier; Chamorro, Jacobo; Littarelli, Sergio A.; Solanes, Aleix; Ramella-Cravaro, Valentina; Vilar, Ana; González-Parra, José A.; Andero, Raül; Reichenberg, Abraham; et al.
Highlights: Reports an umbrella review on risk/protective factors for post-traumatic stress disorder (PTSD). Several risk factors show convincing evidence of association with PTSD. Findings may help optimize prediction and prevention. Abstract: Approximately one third of individuals who experience a severe traumatic event will develop posttraumatic stress disorder (PTSD). It is crucial to identify what factors may be associated with increased or decreased risk for PTSD. We conducted an umbrella review of systematic reviews and meta-analyses of risk/protective factors for PTSD and assessed and graded the evidence of the association between each factor and PTSD. Thirty-three systematic reviews and meta-analyses were included and 130 potential risk factors were identified. Of those, 57 showed a significant association with PTSD. Being female or being indigenous people of the Americas, among the sociodemographic factors; history of physical disease and family history of psychiatric disorder, among the pretrauma factors; and cumulative exposure to potentially traumatic experiences, trauma severity, and being trapped during an earthquake, among the peritrauma factors, showed convincing or highly suggestive evidence of an association with PTSD. Data from prospective studies were less conclusive. Our results have the potential of helping refine PTSD prediction models and contributing to the design of prevention strategies.